Reduced extrinsic recombination process in anatase and rutile TiO2 epitaxial thin films for efficient electron transport layers - Yeon Soo Kim; Hye-Jin Jin; Hye Ri Jung; Jihyun Kim; Bich Phuong Nguyen; Juran Kim; William Jo (Scientific Reports, 2021)
Abstract TiO2 is the most widely used material for the electron transport layers (ETLs) because it is characterized by proper band alignment with light absorbers, adequate optical transmittance, and high electron mobility. There are two thermodynamically stable crystal phases of TiO2: anatase and rutile. However, understanding which phase is more effective as the ETL is still required. In this paper, we demonstrate the different effects of using epitaxial anatase TiO2 and epitaxial rutile TiO2 (both grown using pulsed laser deposition) as the ETL material on the electrical and optical properties. Epitaxial Nb-doped TiO2 layers were used as the common electrode material for the both epitaxial ETLs for which the crystalline structural analysis revealed high crystalline qualities and good coherency for both phases. By analyzing the recombination kinetics, the anatase phase shows a preferable performance in comparison with the rutile phase, although both epitaxial phases show remarkably reduced extrinsic recombination properties, such as trap-assisted recombination. This study demonstrates not only a better electron transporting performance of anatase phase but also reduced extrinsic recombination through epitaxy growth.